Environmental Health Determinants Related To The Incidence Of Stunting In Toddlers In The Work Area Of The Siatas Barita Community Health Center North Tapanuli Regency - Parapat, Tetty U. H.; Fadlilah Widyaningsih; Monika Helen Sinaga (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Indonesia experiences a double burden of malnutrition, where on the one hand the prevalence of undernutrition is still high while on the other hand the prevalence of overnutrition is no less high The incidence of stunting is caused by many factors that affect each other and the causes can be different in each region. Objectives: to analyze environmental health determinants related to the incidence of stunting in toddlers in the work area of the Siatas Barita Health Center, North Tapanuli Regency. Research method: quantitative research that is an analytical survey with a cross sectional design which aims to analyze the determinants of environmental health factors related to the incidence of stunting in toddlers in the working area of the Siatas Barita Health Center, North Tapanuli Regency. Results: there was a relationship between drinking water, family latrines, wastewater disposal, garbage disposal facilities, and the incidence of stunting in toddlers Conclusion: The environmental health factors that are most related to the incidence of stunting in toddlers in the work area of the Siatas Barita Health Center, North Tapanuli Regency are wastewater disposal and waste disposal facilities. Keywords: Stunting, environmental health, toddlers